Effect of probiotic co-cultures on physico-chemical and biochemical properties of small ruminants' fermented milk - Francisco X. Malcata (2017)
Small ruminants' fermented probiotic milk is an alternative to fermented cows' milk, especially because of the monounsaturated/polyunsaturated fatty acid profiles. The technological and biochemical potential of Bifidobacterium and Lactobacillus co-cultures, with or without inulin, on goats' and ewes' milk was assessed. Microbial stability, lactose consumption, organic acid production, proteolytic parameters and conjugated linoleic acid (CLA) production in situ, were followed in ewes' and goats' fermented milk (EFM and GFM, respectively) over 21 days at 4 C; technological feasibility for probiotic fermented milk production was shown. In EFM, all co-cultures presented high viable cell numbers (>7.0 log cfu mL1 ) throughout storage, presenting faster acidification capacities and higher CLA isomer levels than in GFM. Inulin had no impact on probiotic growth, yet contributed to storage stability. CLA isomers and proteolysis indices were co-culture dependent traits: for example, co-culture of Bifidobacterium animalis B94 with Lactobacillus acidophilus L10 registered the best CLA-production in GFM. (c) 2017 Elsevier Ltd. All rights reserved.